ANALYSIS OF PROFITABILITY OF SHARIA INSURANCE COMPANIES IN INDONESIA - Riskayanti, Riskayanti; Rini Purnamasari (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2023)
The sharia insurance industry in Indonesia experienced a decline in profits in 2020. This research was conducted to further analyze the performance of sharia insurance companies in generating profits in 2020 as measured by profitability ratios. Profitability ratios consist of Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Equity (ROE), and Return on Assets (ROA). This research is a type of descriptive quantitative research and data collection uses documentation techniques by taking secondary data in the form of sharia insurance company financial reports in 2020 which are available on the Financial Services Authority (OJK) website. The number of companies studied was thirteen companies. The results of this research show that: the profitability of sharia insurance companies in 2020, both in terms of gross profit margin (GPM), net profit margin (NPM), return on equity ratio (ROE), and return on assets ratio (ROA), is in poor condition , because the average value of GPM, NPM, ROE and ROA for sharia insurance companies is below 12%. The average GPM value of sharia insurance companies in 2020 was 0.86%, NPM was 0.76%, ROE was 0.35%, and ROA was 0.27%. Based on the results of calculating these four ratios, the performance of sharia insurance companies is still less than optimal in generating profits because the values ​​of the four profitability ratios are below the average standard of 12% Keywords : Profitability, GPM, NPM, ROE, ROA